2015
DOI: 10.1111/cas.12639
|View full text |Cite
|
Sign up to set email alerts
|

Advanced human T‐cell leukemia virus type 1 carriers and early‐stage indolent adult T‐cell leukemia‐lymphoma are indistinguishable based on CADM1 positivity in flow cytometry

Abstract: We previously reported that the cell adhesion molecule 1 (CADM1) versus CD7 plot in flow cytometry reflects disease progression in human T-cell leukemia virus type 1 (HTLV-1) infection. In CD4+ cells from peripheral blood, CADM1−CD7+ (P), CADM1+CD7dim (D) and CADM1+CD7− (N) subpopulations are observed. The D and N subpopulations increase as asymptomatic HTLV-1 carriers (AC) progress to indolent adult T-cell leukemia-lymphoma (ATL) and the N subpopulation then expands in aggressive ATL. In the present study we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 30 publications
4
29
0
Order By: Relevance
“…For the elderly patients, the development of new, less toxic agents such as mAbs or small molecule agents, rather than intensive cytotoxic therapies, are urgently needed. Furthermore, any strategies for preventing the development of ATL in HTLV‐1 carriers by identifying definite markers for high‐risk HTLV‐1 carriers using, for example, multicolor flow cytometry is also needed …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the elderly patients, the development of new, less toxic agents such as mAbs or small molecule agents, rather than intensive cytotoxic therapies, are urgently needed. Furthermore, any strategies for preventing the development of ATL in HTLV‐1 carriers by identifying definite markers for high‐risk HTLV‐1 carriers using, for example, multicolor flow cytometry is also needed …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, any strategies for preventing the development of ATL in HTLV-1 carriers by identifying definite markers for high-risk HTLV-1 carriers using, for example, multicolor flow cytometry is also needed. (33)…”
Section: Discussionmentioning
confidence: 99%
“…We recently took advantage of the universal expression of CADM1 in HTLV‐1‐infected cells and the downregulation of CD7 expression based on the oncogenic stage of HTLV‐1‐infected cells to develop a flow cytometric system using CADM1 versus CD7 plotting of CD4 + cells (named the HTLV‐1 analysis system by flow cytometry [HAS‐Flow]). We previously reported that HAS‐Flow enables an objective evaluation of the clinical disease progression of AC and indolent ATL cases …”
Section: Introductionmentioning
confidence: 99%
“…ATL cells often share the Treg phenotype, i.e., CD3 þ CD4 þ CD25 þ Foxp3 þ (8,9). Although ATL cells may be defined by their expression of CADM1 (10,11), the overlap and differences between Tregs and ATL cells remain unclear.…”
Section: Introductionmentioning
confidence: 99%